Master tracks in different resolutions of METEOR cruise M211, Nice - Ponta Delgada, 2025-06-14 - 2025-07-26 - Oliver Wurl (PANGAEA, 2025)
Raw data acquired by position sensors on board RV METEOR during expedition M211 were processed to receive a validated master track which can be used as reference of further expedition data. During M211 the motion reference unit Kongsberg SeaTex AS MRU-5 combined with Kongsberg SeaTex AS Seapath 320 and two SAAB R6 DGPS receiver were used as navigation sensors. Data were downloaded from DAVIS SHIP data base (https://dship.bsh.de) with a resolution of 1 sec. Processing and evaluation of the data is outlined in the data processing report. Processed data are provided as a master track with 1 sec resolution derived from the position sensors extquotesingle data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.